The Influence of Social Media Marketing on Brand Image and Purchase Intention for Halal Products - Atika Widya Utama; Meera Gupta; Rohan Kumar (Yayasan Adra Karima Hubbi, 2025)
Social media marketing has become a powerful tool for shaping brand image and influencing consumer behavior, particularly in the context of halal products. As the global demand for halal products continues to grow, understanding how social media marketing impacts brand image and purchase intention is critical for businesses targeting Muslim consumers. However, limited research has explored this relationship, especially in emerging markets where halal product consumption is rapidly increasing. This study aims to examine the influence of social media marketing on brand image and purchase intention for halal products, providing insights into how businesses can leverage social media to enhance consumer engagement and drive sales. A quantitative research design was employed, utilizing survey data collected from 300 Muslim consumers in Indonesia. Structural equation modeling (SEM) was used to analyze the relationships between social media marketing, brand image, and purchase intention. The findings reveal that social media marketing significantly enhances brand image (? = 0.52, p < 0.001) and purchase intention (? = 0.48, p < 0.001). Brand image also mediates the relationship between social media marketing and purchase intention, indicating its pivotal role in influencing consumer decisions. This study highlights the importance of social media marketing in building a positive brand image and driving purchase intention for halal products. The results suggest that businesses should prioritize engaging and authentic social media strategies to attract and retain Muslim consumers.